2016
DOI: 10.1002/app.43310
|View full text |Cite
|
Sign up to set email alerts
|

Reactive modification and compatibilization of poly(lactide) and poly(butylene adipate‐co‐terephthalate) blends with epoxy functionalized‐poly(lactide) for blown film applications

Abstract: Biodegradable blown films comprising of poly(lactide) (PLA) and poly(butylene adipate‐co‐terephthalate) (PBAT) were produced using epoxy functionalized‐poly(lactide) (EF‐PLA) reactive modifiers for rheological enhancement and compatibilization. The epoxy groups on the EF‐PLA modifiers react with PBAT forming an in situ copolymer that localizes at the blend interphase resulting in compatibilization of the polymer blend components. The EF‐PLA modified polymer blends have improved melt strength and the resultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…showed the results of SEM micrographs. It was well‐known that PLA/PBAT was immiscible because of the poor adhesive attraction . As we can see from Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…showed the results of SEM micrographs. It was well‐known that PLA/PBAT was immiscible because of the poor adhesive attraction . As we can see from Fig.…”
Section: Resultsmentioning
confidence: 71%
“…In the past decade, increasing attention has been paid to the biodegradable polymers because of their renewable resources and friendly impact on the environment. Poly(lactic acid) (PLA) is a biobased and biodegradable/compostable polymer derived from corn . PLA is a promising aliphatic polyester in these biosourced polymers owing to its relatively high mechanical strength, excellent optical properties, and processability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider et al [92] prepared blown films from PLA and PBAT were produced using an epoxy functionalized-poly(lactide) (EF-PLA) in order to provide some degree of compatibilization (through the epoxy groups reacting with the PBAT) as well as an improvement of the rheological properties. They found that the compatibilizer enhanced the melt strength, thus allowing use of higher PLA amounts (up to 70%) and especially to have higher bubble stability.…”
Section: Processing Of Films Based On Biodegradable Polymersmentioning
confidence: 99%
“…These observations corresponded with the results presented by Arruda et al [107] who studied PLA/PBAT blends compatibilized by chain extender Joncryl ® (BASF). Recently, Schneider et al [108] used epoxy functionalized-PLA (EF-PLA) as reactive modifier for PLA/PBAT blends. During reactive extrusion in-situ copolymerization takes place between the epoxy groups present in the EF-PLA modifier and carbonylend groups in PBAT resulting in strong interphase adhesion between blended components and consequently improve mechanical, rheological and morphological properties of PLA/PBAT blends.…”
Section: Aliphatic Polyesters Blendsmentioning
confidence: 99%